Liquid crystal dimming film with ceramic hardened coating
By applying a ceramic hardened coating on the liquid crystal dimming film, using components such as organic-inorganic composite silicone resin and nanofillers, the problem of insufficient hardness and weather resistance of the liquid crystal dimming film is solved, and high hardness and good light transmission are achieved Rate and longevity effects.
Patent Information
- Application Number
- CN202411459663.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-17
AI Technical Summary
The existing liquid crystal dimming films have shortcomings in weather resistance and hardness, resulting in short service life, and methods of increasing polymer coatings will sacrifice light transmittance and response speed, and cannot effectively resist ultraviolet aging.
Using ceramic hardened coating, ceramic water paint is formed through organic-inorganic composite silicone resin, nanofiller, wear-resistant filler and film-enhancing resin and other components, and is coated onto the liquid crystal dimming film to improve hardness and weather resistance. and light transmittance, enhancing the bonding power of the coating and the film.
It realizes that the hardness and weather resistance of the liquid crystal dimming film can be improved while ensuring light transmittance, can resist scratches and wear, extend service life, and maintain good working performance.
Smart Images

Figure BDA0005091511300000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of liquid crystal dimming films, and in particular to a liquid crystal dimming film with a ceramic hardened coating. Background Art
[0002] As a new type of optical material, liquid crystal dimming film has been widely used in the fields of smart buildings and automobiles in recent years due to its unique optical control function. Liquid crystal dimming film adjusts the light transmittance by changing the optical state of the film, providing users with a convenient and personalized control experience. With the increase in market demand, people continue to optimize the performance of liquid crystal dimming film.
[0003] Existing liquid crystal dimming films generally have problems such as poor weather resistance and short service life due to insufficient hardness. Existing technical means mainly enhance hardness by adding polymer coating, but this approach often sacrifices light transmittance and response speed, and cannot effectively resist aging caused by long-term ultraviolet radiation, so it needs to be improved. Summary of the invention
[0004] In order to improve the hardness and weather resistance of the liquid crystal dimming film while ensuring the transmittance, the present application provides a liquid crystal dimming film with a ceramic hardened coating.
[0005] The liquid crystal dimming film with a ceramic hardened coating provided in the present application adopts the following technical solution: A liquid crystal dimming film with a ceramic hardened coating, comprising a liquid crystal dimming film and a ceramic hardened coating, wherein the ceramic hardened coating is obtained by coating a ceramic water paint, and the raw materials for preparing the ceramic water paint include the following components in parts by mass: 40-60 parts of organic-inorganic composite silicone resin 4-8 parts of anti-reflective nanofiller 2-5 parts of wear-resistant filler 1-2 parts of extender 20-30 parts of anti-reflection film-forming resin Dispersant 1-3 parts Defoaming agent 0.5-1 part Leveling agent 0.5-1 part 30-50 parts of water.
[0006] Organic-inorganic composite silicone resin improves the compatibility of ceramic water paint system through the combination of organic and inorganic phase components, effectively improves the hardness and weather resistance of ceramic hardened coating, and enhances the bonding force between coating and liquid crystal dimming film. In addition, the organic phase and inorganic phase are evenly distributed inside the organic-inorganic composite silicone resin and reinforce each other, which reduces the refractive index, reduces the scattering and absorption of light, and improves the crystallinity and transparency of the material, thereby enhancing the light transmittance. The anti-reflective nano-filler and anti-reflective film-forming resin have good light transmittance, can reinforce internal molecular defects, improve the film-forming performance of ceramic water paint, and effectively improve the light transmittance of ceramic hardened coating. The wear-resistant filler can enhance the hardness and wear resistance of the surface, so that the liquid crystal dimming film can resist daily scratches and wear, and extend its service life. The liquid crystal dimming film with ceramic hardened coating has good light transmittance, weather resistance and high hardness, can resist scratches and wear, and maintain good working performance for a long time.
[0007] Preferably, the raw materials for preparing the organic-inorganic composite silicone resin include tetraethyl orthosilicate, thiosiloxane, cage-type silsesquioxane and epoxy silane coupling agent.
[0008] As a precursor, tetraethyl orthosilicate is hydrolyzed to form an inorganic network structure of silicon dioxide, which improves the hardness of the material. The uniformly dispersed inorganic phase formed can effectively reduce the scattering of light and improve the transmittance of the ceramic hardened coating; the introduction of sulfur-based siloxane can enhance the weather resistance and stability of the material; cage-type silsesquioxane has a unique three-dimensional structure, which not only further improves the hardness of the material, but also reduces the disordered arrangement of molecular chains, reduces the scattering and absorption of light, and thus improves the transmittance; epoxy silane coupling agent acts as a bridge to connect the organic phase and the inorganic phase, promotes the close bonding between the phases, reduces interface defects, enhances the overall performance of the material, and can effectively improve the transmittance; through the synergistic effect of each component, the organic-inorganic composite silicone resin effectively improves the hardness, weather resistance and transmittance of the ceramic hardened coating.
[0009] Preferably, the organic-inorganic composite silicone resin is prepared by the following steps: Dispersing tetraethyl orthosilicate in anhydrous ethanol, stirring and dispersing to obtain a tetraethyl orthosilicate solution, adding deionized water to the tetraethyl orthosilicate solution, adjusting the pH to acidic after heating, adding thiosiloxane to the solution after adjusting the pH, heating and stirring to react to obtain silica sol; adding a hydrogen peroxide aqueous solution to the silica sol, stirring and reacting to obtain a sulfonated silica sol; adding an epoxy silane coupling agent to the sulfonated silica sol, stirring and reacting, adding cage-type silsesquioxane and benzoyl peroxide, stirring and reacting in a water bath, and removing the solvent by rotary evaporation to obtain an organic-inorganic composite silicone resin.
[0010] The organic-inorganic composite silicone resin prepared according to the above steps has good hardness, weather resistance and light transmittance; after the introduction of sulfur-based siloxane, the sulfur group is oxidized into a sulfonic acid group by strong oxidizing hydrogen peroxide, thereby improving the hydrophilicity and wettability of the organic-inorganic composite siloxane, thereby improving the interface compatibility and stability, and then improving the hardness, weather resistance and light transmittance of the ceramic hardened coating.
[0011] Preferably, the anti-reflection nano-filler includes one or more of nano-indium tin oxide, nano-antimony tin oxide and graphene.
[0012] Nano indium tin oxide and nano antimony tin oxide have high transmittance, which can reduce light scattering and improve the transmittance of ceramic hardened coatings; graphene has excellent optical properties and can enhance the transmittance of light through interference and diffraction, effectively improving the transmittance of coatings; nano indium tin oxide, nano antimony tin oxide and graphene have good chemical stability, which can effectively resist the influence of ultraviolet rays and high temperature environment and improve the weather resistance of coatings; nano indium tin oxide, nano antimony tin oxide and graphene themselves also have high hardness, which can effectively reinforce the structural defects of coatings and improve the hardness and stability of coatings.
[0013] Preferably, the wear-resistant filler includes one or more of boron nitride nanotubes, nano-titanium dioxide and nano-cerium dioxide.
[0014] Boron nitride nanotubes have high strength and hardness. They can effectively disperse stress in the coating and prevent crack propagation, thereby improving the overall hardness. At the same time, they have good chemical stability, which can enhance the weather resistance of the coating and resist the influence of environmental factors such as ultraviolet rays and temperature changes. Nano-titanium dioxide and nano-cerium dioxide improve the hardness of the coating and reduce wear through their own hardness characteristics. They can also absorb ultraviolet rays, quench free radicals, and improve the weather resistance of the coating. When these three nanofillers are evenly dispersed in the coating, they can reduce light scattering and optimize the optical properties of the coating.
[0015] Preferably, the compatibilizer includes one or more of a surfactant and a silane coupling agent.
[0016] Surfactants can reduce the surface tension of filler particles, reduce agglomeration, and make the filler evenly dispersed; silane coupling agents can react with hydroxyl groups on the surface of the filler to form chemical bonds, acting as a bridge between the inorganic and organic phases to enhance interfacial compatibility, thereby enhancing its dispersion performance, and further improving light transmittance, and enhancing the hardness and weather resistance of the coating.
[0017] Preferably, the anti-reflection film-forming resin includes polyurethane resin emulsion and fluorocarbon resin solution.
[0018] Polyurethane resin emulsion has good film-forming properties and flexibility. It can form a tight molecular network during the film-forming process, promote the ceramic water paint to form a uniform coating on the surface of the liquid crystal dimming film, fill the tiny pores and defects on the surface, and improve the surface flatness, thereby reducing light scattering and improving light transmittance; fluorocarbon resin solution has low surface energy and excellent weather resistance. The fluorine atoms in fluorocarbon resin have strong electronegativity and can be tightly arranged on the molecular surface to form a dense protective layer, which effectively prevents the invasion of moisture, oxygen and other corrosive substances and improves the weather resistance of the coating; at the same time, the low surface energy makes the coating have good self-cleaning properties and reduces the adhesion of dust and stains; fluorocarbon resin solution can optimize optical properties, reduce light reflection and refraction losses, thereby improving light transmittance.
[0019] Preferably, the raw materials for preparing the polyurethane resin emulsion include hydrophilic monomers, isocyanate and bio-based sugar alcohol chain extender.
[0020] Isocyanate reacts with hydrophilic monomers and bio-based sugar alcohol chain extenders to form a tight molecular network structure, which improves the strength and hardness of the coating after film formation and protects the surface of the liquid crystal dimming film; the introduction of bio-based sugar alcohol chain extenders brings better stability and durability to the polyurethane resin emulsion, the rigid spirocyclic structure of sugar alcohol can improve the hardness of the coating, the hydroxyl group can improve its wettability and compatibility, and increase the internal cross-linking degree, thereby further improving the hardness and weather resistance.
[0021] Preferably, the raw materials for preparing the fluorocarbon resin solution include tetrafluoroethylene, glycidyl methacrylate and perfluoroacrylate.
[0022] The carbon-fluorine bond in tetrafluoroethylene has high bond energy and is not easy to break or deform, providing rigid support, thereby improving hardness and stability; perfluoroacrylate increases the rigidity and steric hindrance of the molecular chain through the perfluoro group in its side chain, and the epoxy group of glycidyl methacrylate can initiate a cross-linking reaction. The three are cross-linked to form a three-dimensional network structure, which effectively disperses stress, significantly improves the hardness of the resin, and enables the coating to resist scratches and wear; fluorine atoms have a low refractive index, and fluorocarbon resin can reduce light refraction and scattering; fluorocarbon resin has strong stability and chemical corrosion resistance, can reduce the surface energy of the coating, and improve its weather resistance and stability.
[0023] Preferably, the liquid crystal dimming film with ceramic hardening coating is prepared by the following steps: The anti-reflection nanofiller, the wear-resistant filler and the compatibilizer are mixed and dispersed in anhydrous ethanol to obtain a modified mixed solution, deionized water is added to the modified mixed solution, and after stirring for reaction, a mixture is obtained by filtering, and the mixture is dried to obtain a modified filler; Dispersing an organic-inorganic composite silicone resin and a dispersant into water, adding an anti-reflection film-forming resin, stirring and dispersing, adding the modified filler prepared above, stirring to obtain a mixed solution, homogenizing and grinding the mixed solution, adding a defoamer and a leveling agent to the homogenized mixed solution, and stirring to obtain a ceramic water paint; The ceramic water paint is applied to the surface of the liquid crystal dimming film through a slit, and after baking and curing, a liquid crystal dimming film with a ceramic hardened coating is obtained.
[0024] The liquid crystal dimming film with a ceramic hardened coating prepared according to the above steps has good hardness, weather resistance and light transmittance, is resistant to scratches and wear, and maintains good working performance for a long time.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Organic-inorganic composite silicone resin improves the compatibility of ceramic water paint system through the combination of organic and inorganic phase components, effectively improves the hardness and weather resistance of ceramic hardened coating, and enhances the bonding force between coating and liquid crystal dimming film. In addition, the organic phase and inorganic phase are evenly distributed inside the organic-inorganic composite silicone resin, and they reinforce each other, which reduces the refractive index, reduces the scattering and absorption of light, and improves the crystallinity and transparency of the material, thereby enhancing the light transmittance. The anti-reflective nano-filler and anti-reflective film-forming resin have good light transmittance, can reinforce internal molecular defects, improve the film-forming performance of ceramic water paint, and effectively improve the light transmittance of ceramic hardened coating. The wear-resistant filler can enhance the hardness and wear resistance of the surface, so that the liquid crystal dimming film can resist daily scratches and wear, and extend its service life. The liquid crystal dimming film with ceramic hardened coating has good light transmittance, weather resistance and high hardness, can resist scratches and wear, and maintain good working performance for a long time.
[0026] 2. Ethyl orthosilicate is used as a precursor and hydrolyzes to generate an inorganic network structure of silicon dioxide, which improves the hardness of the material. The uniformly dispersed inorganic phase formed can effectively reduce the scattering of light and improve the transmittance of the ceramic hardened coating. The introduction of sulfur-based siloxane can enhance the weather resistance and stability of the material. Cage-type silsesquioxane has a unique three-dimensional structure, which not only further improves the hardness of the material, but also reduces the disordered arrangement of molecular chains, reduces the scattering and absorption of light, and thus improves the transmittance. The epoxy silane coupling agent acts as a bridge to connect the organic phase and the inorganic phase, promotes the close bonding between the phases, reduces interface defects, enhances the overall performance of the material, and effectively improves the transmittance. Through the synergistic effect of each component, the organic-inorganic composite silicone resin effectively improves the hardness, weather resistance and transmittance of the ceramic hardened coating.
[0027] 3. Polyurethane resin emulsion has good film-forming properties and flexibility. It can form a tight molecular network during the film-forming process, promote the ceramic water paint to form a uniform coating on the surface of the liquid crystal dimming film, fill the tiny pores and defects on the surface, and improve the surface flatness, thereby reducing light scattering and improving light transmittance; fluorocarbon resin solution has low surface energy and excellent weather resistance. The fluorine atoms in fluorocarbon resin have strong electronegativity and can be tightly arranged on the molecular surface to form a dense protective layer, which effectively prevents the invasion of moisture, oxygen and other corrosive substances and improves the weather resistance of the coating; at the same time, the low surface energy makes the coating have good self-cleaning properties and reduces the adhesion of dust and stains; fluorocarbon resin solution can optimize optical properties, reduce light reflection and refraction losses, thereby improving light transmittance. DETAILED DESCRIPTION
[0028] The present application example discloses a liquid crystal dimming film with a ceramic hardened coating. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the examples: Raw materials description: Ethyl orthosilicate (CAS No.: 78-10-4), thiosiloxane is 3-mercaptopropyltriethoxysilane (CAS No.: 14814-09-6), epoxysilane coupling agent is γ-glycidyloxypropyltrimethoxysilane (CAS No.: 2530-83-8), cage silsesquioxane is octavinyl cage silsesquioxane (CAS No.: 69655-76-1), benzoyl peroxide (CAS No.: 94-36-0), hydrophilic monomers include dimethylol propionic acid (CAS No.: 4767-03-7) and sulfonate polyester polyol BY3303, 4,4'-diphenylmethane diisocyanate (CAS No.: 26447-40-5), the catalyst is dibutyltin dilaurate (CAS No.: 77-58-7), the bio-based sugar alcohol chain extender is isosorbide, triethylamine (CAS No.: 121 -44-8), tetrafluoroethylene (CAS No.: 116-14-3), glycidyl methacrylate (CAS No.: 106-91-2), perfluoroacrylate is perfluorobutylethyl methacrylate (CAS No.: 1799-84-4), azobisisobutyronitrile (CAS No.: 78-67-1), trifluorotoluene (CAS No.: 98-08-8), graphene was purchased from Beijing Graphene Research Institute Co., Ltd., boron nitride nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., sodium dodecyl sulfate (CAS No.: 751-21-3), nano-indium tin oxide, nano-antimony tin oxide, nano-titanium dioxide and nano-cerium dioxide were purchased from Beijing Dekedaojin Technology Co., Ltd., γ-aminopropyltriethoxysilane (CAS No.: 919-30-2), and the silicone resin is Shin-Etsu methyl silicone resin, which was purchased from Suzhou Jiandao Electronics Co., Ltd.
[0029] Example 1 Preparation of organic-inorganic composite silicone resin 52.08 g of tetraethyl orthosilicate was dispersed in 200 mL of anhydrous ethanol, and the mixture was dispersed with stirring at a speed of 200 rpm for 30 min to obtain a tetraethyl orthosilicate solution. 20 mL of deionized water was added to the tetraethyl orthosilicate solution, and the temperature was raised to 60°C. The pH value was adjusted to 4 with concentrated hydrochloric acid. 119.21 g of thiosiloxane was added to the solution after the pH value was adjusted, and the mixture was stirred at a speed of 200 rpm for 4 h at 60°C to obtain a silica sol. 20 0mL of 3% aqueous hydrogen peroxide solution was stirred at 200rpm for 2h to obtain sulfonated silica sol; 236.34g of epoxy silane coupling agent was added to the sulfonated silica sol, and the mixture was stirred at 200rpm for 2h, then 79.13g of cage-type silsesquioxane and 5g of benzoyl peroxide were added, and the mixture was stirred at 200rpm for 2h in a 70°C water bath, and the solvent was removed by rotary evaporation to obtain an organic-inorganic composite silicone resin.
[0030] Preparation of antireflection film-forming resin The hydrophilic monomer is vacuum dehydrated at 110°C, and the mass ratio of dihydroxymethylpropionic acid and sulfonate polyester polyol in the hydrophilic monomer is 1:2 to obtain anhydrous hydrophilic monomer. 60g of anhydrous hydrophilic monomer, 50g of isocyanate and 1g of catalyst are mixed, and stirred at 60°C and 200rpm for 2h under nitrogen protection. 15g of bio-based sugar alcohol chain extender and 0.2g of catalyst are added, and the temperature is raised to 80°C for reaction for 2h. After the reaction is completed, 10g of triethylamine is added, and 50mL of acetone and 150mL of deionized water are added to the system after neutralization. The system is stirred at 1000rpm and the addition is completed within 2h. Acetone is removed by reduced pressure distillation to obtain a polyurethane resin emulsion.
[0031] 40 g of tetrafluoroethylene, 30 g of glycidyl methacrylate, 30 g of perfluoroacrylate and 2 g of azobisisobutyronitrile were dispersed in 200 mL of trifluorotoluene, deoxygenated with nitrogen for 30 min, stirred and reacted at 60 ° C at a speed of 200 rpm for 1 h, and n-hexane was added for purification to obtain a precipitate, which was dispersed in trifluorotoluene to make a mass content of 40% to obtain a fluorocarbon resin.
[0032] Preparation of liquid crystal dimming film with ceramic hard coating 4 g of anti-reflection nanofiller, 2 g of wear-resistant filler and 1 g of a compatibilizer are mixed and dispersed in 20 mL of anhydrous ethanol, the anti-reflection nanofiller is graphene, the wear-resistant filler is boron nitride carbon nanotubes, and the compatibilizer is sodium dodecyl sulfate to obtain a modified mixed solution, 1 mL of deionized water is added to the modified mixed solution within 1 hour, the reaction is stirred at a speed of 200 rpm, and the mixture is filtered to obtain the mixture, and the mixture is dried in an oven at 60°C to obtain a modified filler.
[0033] Disperse 40g of organic-inorganic composite silicone resin and 1g of dispersant in 30mL of water, add 20g of anti-reflection film-forming resin, the mass ratio of polyurethane resin emulsion and fluorocarbon resin solution in the anti-reflection film-forming resin is 1:1, stir and disperse at a speed of 500rpm for 30min, add the modified filler prepared above, stir at a speed of 800rpm for 1h to obtain a mixed solution, transfer the mixed solution to a grinder for homogenization and grinding for 2h, add 0.5g of defoamer and 0.5g of leveling agent to the homogenized mixed solution, stir at a speed of 200rpm for 15min to obtain ceramic water paint.
[0034] The ceramic water paint is applied to the surface of the liquid crystal dimming film through a slit, and after baking and curing, a liquid crystal dimming film with a ceramic hardened coating is obtained.
[0035] Example 2 Preparation of organic-inorganic composite silicone resin 52.08 g of tetraethyl orthosilicate was dispersed in 200 mL of anhydrous ethanol, and the mixture was dispersed with stirring at a speed of 200 rpm for 30 min to obtain a tetraethyl orthosilicate solution. 20 mL of deionized water was added to the tetraethyl orthosilicate solution, and the temperature was raised to 60°C. The pH value was adjusted to 4 with concentrated hydrochloric acid. 119.21 g of thiosiloxane was added to the solution after the pH value was adjusted, and the mixture was stirred at a speed of 200 rpm for 4 h at 60°C to obtain a silica sol. 20 0mL of 3% aqueous hydrogen peroxide solution was stirred at 200rpm for 2h to obtain sulfonated silica sol; 236.34g of epoxy silane coupling agent was added to the sulfonated silica sol, and the mixture was stirred at 200rpm for 2h, then 79.13g of cage-type silsesquioxane and 5g of benzoyl peroxide were added, and the mixture was stirred at 200rpm for 2h in a 70°C water bath, and the solvent was removed by rotary evaporation to obtain an organic-inorganic composite silicone resin.
[0036] Preparation of antireflection film-forming resin The hydrophilic monomer is vacuum dehydrated at 110°C, and the mass ratio of dihydroxymethylpropionic acid and sulfonate polyester polyol in the hydrophilic monomer is 1:2 to obtain anhydrous hydrophilic monomer. 60g of anhydrous hydrophilic monomer, 50g of isocyanate and 1g of catalyst are mixed, and stirred at 60°C and 200rpm for 2h under nitrogen protection. 15g of bio-based sugar alcohol chain extender and 0.2g of catalyst are added, and the temperature is raised to 80°C for reaction for 2h. After the reaction is completed, 10g of triethylamine is added, and 50mL of acetone and 150mL of deionized water are added to the system after neutralization. The system is stirred at 1000rpm and the addition is completed within 2h. Acetone is removed by reduced pressure distillation to obtain a polyurethane resin emulsion.
[0037] 40 g of tetrafluoroethylene, 30 g of glycidyl methacrylate, 30 g of perfluoroacrylate and 2 g of azobisisobutyronitrile were dispersed in 200 mL of trifluorotoluene, deoxygenated with nitrogen for 30 min, stirred and reacted at 60 ° C at a speed of 200 rpm for 1 h, and n-hexane was added for purification to obtain a precipitate, which was dispersed in trifluorotoluene to make a mass content of 40% to obtain a fluorocarbon resin.
[0038] Preparation of liquid crystal dimming film with ceramic hard coating 8 g of anti-reflection nanofiller, 5 g of wear-resistant filler and 2 g of compatibilizer are mixed and dispersed in 30 mL of anhydrous ethanol, the anti-reflection nanofiller is a mixture of nano-indium tin oxide and nano-antimony tin oxide in a mass ratio of 1:1, the wear-resistant filler is a mixture of nano-titanium dioxide and nano-cerium dioxide in a mass ratio of 1:1, and the compatibilizer is γ-aminopropyltriethoxysilane to obtain a modified mixed solution, 1 mL of deionized water is added to the modified mixed solution within 1 hour, the reaction is stirred at a speed of 200 rpm, and the mixture is filtered to obtain the mixture, and the mixture is dried in an oven at 60°C to obtain a modified filler.
[0039] Disperse 60g of organic-inorganic composite silicone resin and 3g of dispersant in 50mL of water, add 30g of anti-reflection film-forming resin, the mass ratio of polyurethane resin emulsion and fluorocarbon resin solution in the anti-reflection film-forming resin is 1:1, stir and disperse at a speed of 500rpm for 30min, add the modified filler prepared above, stir at a speed of 800rpm for 1h to obtain a mixed solution, transfer the mixed solution to a grinder for homogenization and grinding for 2h, add 1g of defoamer and 1g of leveling agent to the homogenized mixed solution, stir at a speed of 200rpm for 15min to obtain ceramic water paint.
[0040] The ceramic water paint is applied to the surface of the liquid crystal dimming film through a slit, and after baking and curing, a liquid crystal dimming film with a ceramic hardened coating is obtained.
[0041] Example 3 Preparation of organic-inorganic composite silicone resin 52.08 g of tetraethyl orthosilicate was dispersed in 200 mL of anhydrous ethanol, and the mixture was dispersed with stirring at a speed of 200 rpm for 30 min to obtain a tetraethyl orthosilicate solution. 20 mL of deionized water was added to the tetraethyl orthosilicate solution, and the temperature was raised to 60°C. The pH value was adjusted to 4 with concentrated hydrochloric acid. 119.21 g of thiosiloxane was added to the solution after the pH value was adjusted, and the mixture was stirred at a speed of 200 rpm for 4 h at 60°C to obtain a silica sol. 20 0mL of 3% aqueous hydrogen peroxide solution was stirred at 200rpm for 2h to obtain sulfonated silica sol; 236.34g of epoxy silane coupling agent was added to the sulfonated silica sol, and the mixture was stirred at 200rpm for 2h, then 79.13g of cage-type silsesquioxane and 5g of benzoyl peroxide were added, and the mixture was stirred at 200rpm for 2h in a 70°C water bath, and the solvent was removed by rotary evaporation to obtain an organic-inorganic composite silicone resin.
[0042] Preparation of antireflection film-forming resin The hydrophilic monomer is vacuum dehydrated at 110°C, and the mass ratio of dihydroxymethylpropionic acid and sulfonate polyester polyol in the hydrophilic monomer is 1:2 to obtain anhydrous hydrophilic monomer. 60g of anhydrous hydrophilic monomer, 50g of isocyanate and 1g of catalyst are mixed, and stirred at 60°C and 200rpm for 2h under nitrogen protection. 15g of bio-based sugar alcohol chain extender and 0.2g of catalyst are added, and the temperature is raised to 80°C for reaction for 2h. After the reaction is completed, 10g of triethylamine is added, and 50mL of acetone and 150mL of deionized water are added to the system after neutralization. The system is stirred at 1000rpm and the addition is completed within 2h. Acetone is removed by reduced pressure distillation to obtain a polyurethane resin emulsion.
[0043] 40 g of tetrafluoroethylene, 30 g of glycidyl methacrylate, 30 g of perfluoroacrylate and 2 g of azobisisobutyronitrile were dispersed in 200 mL of trifluorotoluene, deoxygenated with nitrogen for 30 min, stirred and reacted at 60 ° C at a speed of 200 rpm for 1 h, and n-hexane was added for purification to obtain a precipitate, which was dispersed in trifluorotoluene to make a mass content of 40% to obtain a fluorocarbon resin.
[0044] Preparation of liquid crystal dimming film with ceramic hard coating 6 g of anti-reflection nanofiller, 3.5 g of wear-resistant filler and 1.5 g of compatibilizer are mixed and dispersed in 30 mL of anhydrous ethanol, the anti-reflection nanofiller is a mixture of nano-indium tin oxide, nano-antimony tin oxide and graphene in a mass ratio of 1:1:1, the wear-resistant filler is a mixture of boron nitride nanotubes, nano-titanium dioxide and nano-cerium dioxide in a mass ratio of 1:1:1, and the compatibilizer is a mixture of sodium dodecyl sulfate and γ-aminopropyltriethoxysilane in a mass ratio of 1:1, to obtain a modified mixed solution, 1 mL of deionized water is added to the modified mixed solution within 1 hour, the reaction is stirred at a speed of 200 rpm, and the mixture is filtered to obtain the mixture, and the mixture is dried in an oven at 60°C to obtain a modified filler.
[0045] Disperse 50g of organic-inorganic composite silicone resin and 2g of dispersant in 40mL of water, add 25g of anti-reflection film-forming resin, the mass ratio of polyurethane resin emulsion and fluorocarbon resin solution in the anti-reflection film-forming resin is 1:1, stir and disperse at a speed of 500rpm for 30min, add the modified filler prepared above, stir at a speed of 800rpm for 1h to obtain a mixed solution, transfer the mixed solution to a grinder for homogenization and grinding for 2h, add 0.75g of defoaming agent and 0.75g of leveling agent to the homogenized mixed solution, stir at a speed of 200rpm for 15min to obtain ceramic water paint.
[0046] The ceramic water paint is applied to the surface of the liquid crystal dimming film through a slit, and after baking and curing, a liquid crystal dimming film with a ceramic hardened coating is obtained.
[0047] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, no sulfur-based siloxane is added when preparing the organic-inorganic composite silicone resin.
[0048] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, no epoxy silane coupling agent and cage silsesquioxane are added when preparing the organic-inorganic composite silicone resin.
[0049] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, no bio-based sugar alcohol chain extender is added when preparing the polyurethane resin emulsion.
[0050] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that tetrafluoroethylene is not added when preparing the fluorocarbon resin emulsion in Example 7.
[0051] Comparative Example 1 Comparative Example 1 is based on Example 3. The only difference between Comparative Example 1 and Example 3 is that the organic-inorganic composite silicone resin is replaced by organic silicone resin in Comparative Example 1. Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that no anti-reflection nanofiller is added in Comparative Example 2.
[0052] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that no wear-resistant filler is added in Comparative Example 3.
[0053] Comparative Example 4 Comparative Example 4 is based on Example 3, and the only difference between Comparative Example 4 and Example 3 is that no compatibilizer is added in Comparative Example 4.
[0054] Comparative Example 5 Comparative Example 5 is based on Example 3, and the only difference between Comparative Example 5 and Example 3 is that the anti-reflection film-forming resin in Comparative Example 5 is replaced by a polyurethane resin emulsion.
[0055] Performance testing (1) GB / T 6739-2006 Determination of film hardness of paints and varnishes by pencil method was selected as the standard to test the pencil hardness level of the ceramic hardened coating when scratches appear. The results are recorded in Table 1.
[0056] (2) Select "GB / T 2410-2008 Determination of light transmittance and haze of plastic transparent materials" as the standard to test the light transmittance of the ceramic hardened coating. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.
[0057] (3) Select "GB / T 1865-2009 Paints and varnishes - Artificial weathering and artificial radiation exposure to filtered xenon arc radiation" as the standard. After 2000 hours of artificial accelerated aging, the powdering grade and discoloration grade of the ceramic hardened coating are recorded. The results are recorded in Table 1.
[0058] Table 1 Test results of hardness, light transmittance and weather resistance of ceramic hardened coating It can be seen from Table 1 that the pencil hardness level of Examples 1-3 is 5H, the transmittance is greater than 94.5%, the gloss loss level after aging is level 0, and the powdering level is level 0. It can be seen that the ceramic hardened coating prepared in the present application has good hardness, transmittance and weather resistance, and can effectively improve the scratch and wear resistance of the liquid crystal dimming film, so that it can maintain good working performance for a long time.
[0059] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that: in Example 4, no sulfur-based siloxane is added when preparing the organic-inorganic composite silicone resin, and in Example 5, no epoxy silane coupling agent and cage-type silsesquioxane are added when preparing the organic-inorganic composite silicone resin. Compared with Example 3, Examples 4 and 5 have reduced hardness and transmittance. This is because the synthetic components of the organic-inorganic composite silicone resin are changed, which will affect the compatibility and stability of the coating. The change in the arrangement of the molecular chains will affect the refraction and scattering of light. The reduction in the rigid structure will reduce the hardness of the coating, and then the transmittance and hardness will decrease.
[0060] As shown in Table 1, the only difference between Examples 6 and 7 and Example 3 is that: in Example 6, no bio-based sugar alcohol chain extender is added when preparing the polyurethane resin emulsion, and in Example 7, no tetrafluoroethylene is added when preparing the fluorocarbon resin emulsion. Compared with Example 3, Examples 6 and 7 have reduced hardness and transmittance. This is because the components in the anti-reflection film-forming resin are changed. If the polyurethane resin emulsion does not add the bio-based sugar alcohol chain extender, the rigid spirocyclic structure is lacking and the number of hydroxyl groups is reduced, the internal crosslinking degree and wettability are reduced, and the stability is reduced; if tetrafluoroethylene is not added to the fluorocarbon resin, the rigid structure is lacking in support, the stability is reduced, and the molecular arrangement is changed, so that the hardness and transmittance are reduced.
[0061] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that: Comparative Example 1 replaces the organic-inorganic composite silicone resin with an organic silicone resin. Compared with Example 3, the hardness and transmittance of Comparative Example 1 are significantly reduced; this is because the organic-inorganic composite silicone resin is replaced with an organic silicone resin, lacking the introduction of an inorganic phase silica network, and the ability to regulate optical properties is weakened, the hardness is reduced, and thus the hardness and transmittance are reduced.
[0062] As can be seen from Table 1, the only difference between Comparative Examples 2, 3, and 4 and Example 3 is that: Comparative Example 2 does not add anti-reflection nanofiller, Comparative Example 3 does not add wear-resistant filler, and Comparative Example 4 does not add a compatibilizer. Compared with Example 3, Comparative Examples 2, 3, and 4 have decreased hardness and transmittance; this is because if no anti-reflection nanofiller is added, the refraction and scattering of light will increase, and the reinforcement effect on the inside of the coating will decrease; if no wear-resistant filler is added, the hardness will decrease and scratches will be more likely to appear; due to the lack of the effect of the compatibilizer, the dispersion and compatibility of the filler will decrease, affecting the microstructure inside the coating, and then affecting the hardness and transmittance.
[0063] It can be seen from Table 1 that the only difference between Comparative Example 5 and Example 3 is that the anti-reflection film-forming resin is replaced by a polyurethane resin emulsion in Comparative Example 5. Compared with Example 3, the hardness, light transmittance and weather resistance of Comparative Example 5 are reduced. This is because the reflection and refraction losses of light increase and the surface energy rise due to the lack of fluorocarbon resin, thereby reducing the hardness, light transmittance and weather resistance.
[0064] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A liquid crystal dimming film with a ceramic hardened coating, characterized in that: It includes a liquid crystal dimming film and a ceramic hardening coating, wherein the ceramic hardening coating is obtained by coating ceramic water paint, and the raw materials for preparing the ceramic water paint include the following components in parts by mass: 40-60 parts of organic-inorganic composite silicone resin 4-8 parts of anti-reflective nanofiller 2-5 parts of wear-resistant filler 1-2 parts of extender 20-30 parts of anti-reflection film-forming resin Dispersant 1-3 parts Defoaming agent 0.5-1 part Leveling agent 0.5-1 part 30-50 parts of water.
2. The liquid crystal dimming film with a ceramic hardened coating according to claim 1, characterized in that: The raw materials for preparing the organic-inorganic composite silicone resin include tetraethyl orthosilicate, thiosiloxane, cage-type silsesquioxane and epoxy silane coupling agent.
3. The liquid crystal dimming film with a ceramic hardened coating according to claim 2, characterized in that: The organic-inorganic composite silicone resin is prepared by the following steps: Dispersing tetraethyl orthosilicate in anhydrous ethanol, stirring and dispersing to obtain a tetraethyl orthosilicate solution, adding deionized water to the tetraethyl orthosilicate solution, adjusting the pH to acidic after heating, adding thiosiloxane to the solution after adjusting the pH, heating and stirring to react to obtain silica sol; adding a hydrogen peroxide aqueous solution to the silica sol, stirring and reacting to obtain a sulfonated silica sol; adding an epoxy silane coupling agent to the sulfonated silica sol, stirring and reacting, adding cage-type silsesquioxane and benzoyl peroxide, stirring and reacting in a water bath, and removing the solvent by rotary evaporation to obtain an organic-inorganic composite silicone resin.
4. The liquid crystal dimming film with a ceramic hardened coating according to claim 1, characterized in that: The anti-reflection nano filler includes one or more of nano indium tin oxide, nano antimony tin oxide and graphene.
5. The liquid crystal dimming film with a ceramic hardened coating according to claim 4, characterized in that: The wear-resistant filler includes one or more of boron nitride nanotubes, nano titanium dioxide and nano cerium dioxide.
6. The liquid crystal dimming film with a ceramic hardened coating according to claim 5, characterized in that: The compatibilizer includes one or more of a surfactant and a silane coupling agent.
7. The liquid crystal dimming film with a ceramic hardened coating according to claim 1, characterized in that: The anti-reflection film-forming resin includes polyurethane resin emulsion and fluorocarbon resin solution.
8. The liquid crystal dimming film with a ceramic hardened coating according to claim 7, characterized in that: The raw materials for preparing the polyurethane resin emulsion include hydrophilic monomers, isocyanate and bio-based sugar alcohol chain extender.
9. The liquid crystal dimming film with a ceramic hardened coating according to claim 7, characterized in that: The raw materials for preparing the fluorocarbon resin solution include tetrafluoroethylene, glycidyl methacrylate and perfluoroacrylate.
10. A liquid crystal dimming film with a ceramic hardened coating according to any one of claims 1 to 9, characterized in that: The liquid crystal dimming film with a ceramic hardened coating is prepared by the following steps: The anti-reflection nanofiller, the wear-resistant filler and the compatibilizer are mixed and dispersed in anhydrous ethanol to obtain a modified mixed solution, deionized water is added to the modified mixed solution, and after stirring for reaction, a mixture is obtained by filtering, and the mixture is dried to obtain a modified filler; Dispersing an organic-inorganic composite silicone resin and a dispersant into water, adding an anti-reflection film-forming resin, stirring and dispersing, adding the modified filler prepared above, stirring to obtain a mixed solution, homogenizing and grinding the mixed solution, adding a defoamer and a leveling agent to the homogenized mixed solution, and stirring to obtain a ceramic water paint; The ceramic water paint is applied to the surface of the liquid crystal dimming film through a slit, and after baking and curing, a liquid crystal dimming film with a ceramic hardened coating is obtained.
Citation Information
Patent Citations
Tetrafluoroethylene copolymer resin for coating and preparation method thereof
CN106674407A
Cited By
Super-weather-resistant powder coating as well as preparation method and application thereof
CN120944434A